Relação do pediatra com mães empoderadas no consultório - José Martins Filho; Simone De Carvalho (Sociedade Brasileira de Pediatria, 2023)
This is an experience report, the purpose of which is to describe the experience of using the Pediatric Care Assessment Questionnaire Based on Perceptions of Maternal Care as an aggregator of Pediatrician guidelines. The results showed that the mothers confidence in pediatric guidelines is an indispensable factor for excellence in monitoring maternal and child health. However, one of the biggest barriers to a better quality of the work of this professional is the insufficient time at the time of the consultation to extend the care to the empowered mother regarding her desire for the professionals support for shared decision-making. The results made explicit the parallels and differences in this dynamic and the need to converge the two sides of this relationship. In this study, we recommend further research in the field of pediatrics with regard to empowered mothers in pediatric clinics, implications and solutions for the excellence of pediatric care.